Domains of the YLS: Do Some Matter More than Others? (Journal of Applied Juvenile Justice Services, 2023)
Data were obtained in Pennsylvania to examine referrals to juvenile courts in the Commonwealth for the 2021-2022 school year that include any felony, misdemeanor or summary offenses that occurred on school property. This study looked at the referrals to see if any of the individual domains of the Youth Level of Service Case Management Inventory 2.0 (YLS/CMI) had more of an effect on how the case was disposed of, which was defined as dismissed or handled informally, or formally adjudicated, in juvenile court. The research found that while the overall YLS risk score influenced juvenile court outcomes, only five of the eight individual domains of the YLS had a significant effect on how a case was processed in juvenile court, which calls into question how closely juvenile probation officers are following the instrument in their practice.